Potential of silicon in the productivity and harm reduction of caterpillar-cartridge in maize plants (Research, Society and Development, 2022)
The effect of silicon application on the induction of plant resistance to pests has been widely discussed, as well as its benefits in plant nutrition. However, it is not yet known which source and dose of this nutrient give maize greater productivity and resistance to caterpillar-cartridge (Spodoptera frugiperda) under semi-arid climate conditions. The objective of this work was to evaluate the effect of sources and doses of silicon on yield and resistance of green maize BRS 3046 plants to S. frugiperda in the conditions of Teresina, PI. Two experiments were carried out, in a randomized block design and split-plot design, with four replications. In experiment I, the plots were constituted by doses of potassium silicate (0.0, 1.0, 2.0, 4.0 and 6.0 L ha-1) and in experiment II, by doses of silicon acid (0.0, 0.5, 1.0, 1.5 and 2.0 kg ha-1), evaluated at 15, 30, 45 and 60 days after emergence. The level of leaf damage, number and percentage of damaged plants, number of live leaves, number of caterpillars on ears, plant height, average ear weight and productivity were evaluated. Potassium silicate and silicon acid, respectively, at doses of up to 6.0 L ha-1 and 2.0 kg ha-1 do not change parameters of resistance to S. frugiperda and yield of BRS 3046 maize. The sources and doses of Si do not provide benefits to productivity and do not attenuate damage caused by S. frugiperda in maize plants, BRS 3046.